KARAKTERISTIK PENDERITA TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS MADUKARA 2 TAHUN 2020 - Bayu Suseno; Ulfatul Latifah (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2021)
Pulmonary tuberculosis is an environment-based disease that is the 10th leading cause of death in the world and Tuberculosis mortality globally is estimated at 1.3 million patients. The incidence of pulmonary tuberculosis in the Madukara 2 Public Health Center work area has increased every year. The increase was calculated from 2017 as many as 13 cases, in 2018 there were 18 cases and in 2019 there were an increase of 30 cases again. The purpose of this study was to knowing patient characteristics for pulmonary tuberculosis in the working area of Public Health Center Madukara 2 in 2017-2019. This study was included in the descriptive study with cross sectional method. The population of this study were all respondents recorded in the Pulmonary Tuberculosis program book at Madukara Health Center 2 from 2017-2019 as many as 61 respondents. Sampling in this study is total sampling. This research was conducted in the middle of a co-19 pandemic, so the data used were secondary data obtained from the Madukara 2 Public Health Center. Based on the results of research on patient characteristics for pulmonary tuberculosis from 2017-2019, there are more males than females, with age categories that are more than 25 years. The category shows the productive age category. The highest education level is elementary school and the type of work is labor, the most sufferers are new cases and the result of sputum examination with the highest BTA + status in 2018 is 61.1%. Public Health Center need to strive for the availability of data precisely to facilitate data processing and increase socialization activities and counseling about tuberculosis to reduce the discovery of new cases each year. And the community needs to increase prevention of cases of pulmonary tuberculosis by using masks for sufferers and maintain the cleanliness of the house from adequate ventilation and lighting conditions.